2009
DOI: 10.1002/jcb.22182
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐3‐mediated cyclic stretch‐induced myoblast apoptosis via a Fas/FasL‐independent signaling pathway during myogenesis

Abstract: Skeletal muscle cells are exposed to mechanical stretch during embryogenesis. Increased stretch may contribute to cell death, and the molecular regulation by stretch remains incompletely understood. The aim of this study was to investigate the effects of cyclic stretch on cell death and apoptosis in myoblast using a Flexercell Strain Unit. Apoptosis was studied by annexin V binding and PI staining, DNA size analysis, electron microphotograph, and caspase assays. Fas/FasL expression was determined by Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…A previous study exploring the connection between mechanical forces and the apoptosis of myoblast cells, found that the stretching pattern could induce the apoptosis of the cells (25), but to date the mechanism of stretch-induced apoptosis of OA-derived chondrocytes remains unclear. In the present study, we hypothesized that the mechanical force could activate Piezo1, further resulting in the apoptosis of OA-derived chondrocytes during the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study exploring the connection between mechanical forces and the apoptosis of myoblast cells, found that the stretching pattern could induce the apoptosis of the cells (25), but to date the mechanism of stretch-induced apoptosis of OA-derived chondrocytes remains unclear. In the present study, we hypothesized that the mechanical force could activate Piezo1, further resulting in the apoptosis of OA-derived chondrocytes during the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the levels of caspase-3, the lower the number of surviving cells [Sandri et al, 2001;Liu et al, 2009;Amna et al, 2013]. We next evaluated apoptosis biochemically by semiquantifying the levels of caspase-3.…”
Section: Effect Of Mechanical Stretch On the Expression Of Caspase-3 mentioning
confidence: 99%
“…Excessive ROS productions induce cell death via activation of Fas (also known as CD95) in human monocytes [12]. Fas activation results in Fas receptor clustering at the plasma membrane and activates caspase-8 which subsequently triggers the proteolytic activations of other caspases, including caspase-3, -6 and -9 [13,14]. The activated caspase-8 cleaves BH3 interacting domain death agonist (Bid) to form truncated Bid (tBid) which induces mitochondrial damage, cell shrinkage, and nuclear condensation [15].…”
Section: Introductionmentioning
confidence: 99%